Exploring the Feasibility of Estrogen Replacement Therapy as a Treatment for Perimenopausal Depression: A Comprehensive Literature Review - Xiuting Xiang; Praneetha Palasuberniam; Rahmawati Pare (MDPI, 2024)
Perimenopausal depression (PMD) is a psychological disorder that occurs in women during perimenopause. In addition to the common clinical symptoms of depression, it often manifests as a perimenopausal complication, and its notable cause is the decline in estrogen levels. Despite numerous studies and trials confirming the benefits of estrogen replacement therapy (ERT) for PMD, ERT remains unapproved for treating PMD. Therefore, we conducted a literature search using selected keywords in PubMed and Google Scholar to write a review discussing the feasibility of using ERT for PMD. This review examines the potential of ERT for PMD in terms of its underlying mechanisms, efficacy, safety, and time window. These four aspects suggest that ERT is a viable option for PMD treatment. However, the risk of thrombosis and stroke with ERT is a matter of contention among medical experts, with a paucity of clinical data. Consequently, further clinical trial data are required to ascertain the safety of ERT.